The evolution of acoustic size exaggeration in terrestrial mammals - Benjamin D. Charlton (Nature Portfolio, 2016)
The acoustic properties of vocal signals generally depend on body size, but in some species males have traits that exaggerate the size conveyed by their vocal signals. Here, Charlton and Reby show that among terrestrial mammals, species with sexual selection for large male body size also have more exaggerated vocal signals for their size.